Early Muslim summer camps in Canada: Spaces of identity formation and belonging - Hughes, Aaron W. (Studies in religion, 2026)
This article presents the first academic study of Muslim summer camps in Canada, examining both their history and purpose. Based primarily on archival research, it situates these Muslim camps against the broader backdrop of (non-Muslim) Canadian summer camps before showing several of their unique aspects. It argues that Muslim summer camps were distinct in the sense that, from their beginning, they played both a religious and a civic role. While helping to form Muslim religious identity through various Islamic activities (e.g. memorization of chapters from the Quran, Islamic arts and crafts), these camps also engaged in traditional pursuits such as canoeing and camp songs to build a sense of civic (i.e. Canadian) identity. The emphasis, then, was on how to engage in "Islamic living" while also being a member of a larger non-Muslim society. In so doing, these camps creatively "and perhaps somewhat paradoxically" used traditional Canadian institutions to build Muslim identity, all the while seeking to form a Muslim identity within a Canadian context. Following this, the article turns to the historical development of these camps over the past 50 years.